Integrated data aggregation with fault-tolerance and lifetime energy-aware adaptive routing in coffee plantations using WSNs - Roshan Zameer Ahmed; Sravani K.; Shilpa S. Chaudhari; S. Sethu Selvi; S. L. Gangadharaiah (Institute of Advanced Engineering and Science, 2021)
The pest namely coffee white stem borer (CWSB) has harmed the economic progress of many emerging countries as a result of arabica coffee’s agricultural products. The boring activity causes the stem to shrink, fade in color, and acquire translucent margins across the stem. The pest multiplier can be controlled by capturing the location with the utilization of a wireless sensor networks (WSNs) and blocking its exit point at the user end. In this work, we propose an integrated data aggregation with faulttolerance and lifetime energy-aware adaptive routing (IDALAR) approach to transfer the sensed pest location data. The efficient packet format and statistical models based routing between clusterheads (CHs) and base station (BS) is proposed considering the availability of resources such as message overhead, algorithmic complexity, residual energy, and control overhead are all used to calculate its performance.